Efficacy of storage duration and pre-sowing treatments on seed germination, seedling growth and longevity of karonda (Carissa carandas) - BARMAN, JAYA; GHOSH, ARKENDU; DEY, KOYEL; DAS, BIKASH CHANDRA; GHOSH, SATYA NARAYAN (The Indian Journal of Agricultural Sciences, 2018)
Considering germination problem in karonda (Carissa carandas L.) the present experiment was carried out in factorial randomized block design with 3 stages of seed storage condition and 12 levels of pre-sowing treatments coupled with 36 treatment combinations. Investigation revealed that freshly shown seeds were superior in respect of germination percentage (64.12%), fresh and dry shoot weight and root weight, seedling vigour index (1411.72) and root-shoot ratio (0.27) also. In case of several pre-sowing treatments, P8 (KNO3 ) gave the maximum germination percentage (55.37%), seedling vigour index (1148.49) with minimum time taken for germination (11.74). The interaction between different storage duration and pre-sowing treatments was statistically significant with respect to germination percentage of Karonda. Among different treatment combination, T8 (D1 P 8 ) recorded best in respect minimum time taken for germination (8.20) and other morphological parameters whereas T36 gave the lowest results in all the parameters observed.